Development of Sustainable Geopolymer Mortar using Industrial Waste Materials. (2016) - Bashar, Iftekhair Ibnul; Alengaram, U. Johnson; Jumaat, Mohd Zamin; Islam, Azizul
Abstract: The utilization of palm-oil-fuel-ash (POFA), fly-ash (FA), and blast-furnace-slag (BFS) as binders and the effects of quarry dust and manufactured sand (M-sand) as replacement for conventional mining sand (N-sand) on compressive strength ( f comp ) of geopolymer mortar were investigated. The calcium rich-BFS increased f comp and 50% POFA with BFS produced 28day f comp of 58 MPa. The use of 100% M-sand in mortar shows comparable f comp with that of prepared with 100% N-sand due to filling and packing ability of former. The use of POFA-FA-BFS and M-sand as binders and fine aggregate, respectively could be a viable alternative to the conventional materials.